Une révolution inachevée - Charles Gadea; Michel Lallement (Temporalités)
Durkheim's Elementary forms of religious life contain a formulation of the foundations of a sociology of time which has constantly sparked the reflections of his successors. He himself did not develop it much further but his followers, Hubert and Mauss, or Halbwachs, drawing their inspiration from a critical reading of Bergson, gave it more scope and substance. Taking off from the way the notion of time intervenes in the critical notes and studies of L’Année sociologique, this papers attemps to retrace the emergence of the notion of time in the Durkheimian school and to locate its earlier positioning.